STUDY ON THE QUALITY AND OMEGA-3 FATTY ACIDS COMPOSITION OF SUPER DRIED CATFISH (Arius talassinus) - Fronthea Swastawati (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Study on the quality and omega-3 fatty acids composition of dried fish was conducted in order to observe the sensory value, proximate composition, and omega-3 fatty acid content of catfish dried by traditional and mechanical dryer. Experimental laboratories method using t-test resulted that both methods of drying fish were available to be implemented. The evaluation of data of appearance using t-test showed that taccount =3.631>ttab(0.05)(6)=2.447. This indicated that the appearance between two products were significantly different. But in general there are no significant differences in odor, taste and texture of products. The product was accepted organoleptically by the panellists with the values of 7.64-8.29. Protein composition of catfish was relatively high : 17.47% and lipid content of 0.73. DHA and EPA values of dried fish using mechanical dryer were 13.8% and 5.1%; whereas traditional dryer were percentage of 12.8% and 7.7%.